Clinical researchDepression in patients with oral or facial malignancy - Rutkowska, Monika; Gerber, Hanna; Nowak, Rafał; Piątkowski, Jan (Archives of Medical Science, 2007)
Arch Introduction: For many years interest in cancer patients concerned mainly their physical state, treatment efficacy and survival time. Meanwhile, a consequence of oncological treatment is physical and mental disability. Anxiety, fear and uneasiness, being the most common reactions to biological and social threat, can lead to severe mental disorders. The incidence of anxiety and depressive disorders in cancer patients ranges from 20 to 80% in different study centres. Polish scientific literature lacks publications dealing with the mental state of patients treated for facial and oral malignancies. Research attempting to evaluate the way a disfiguring procedure aggravates the patient’s mental state is also missing in Polish and foreign academic writing. It is estimated that 20-25% of cancer patients suffer from undiagnosed depression. The aim of the present study was to assess depression level in patients with diagnosed oral and facial malignancy shortly after diagnosis, as well as to pinpoint mental changes caused by extensive surgery. Material and methods: The study was performed one day before surgery, and then 7 days after it, during the convalescence period on 31 patients in the ward. To measure depression severity the Beck Depression Inventory (BDI) was used. Results: Symptoms of depression were found in more than 40% of patients before surgery and 58.5% after it. Conclusions: Surgical treatment of face and neck cancer may increase the level of depression. Patients treated with extensive surgery should be able to obtain professional psychological help both before and after treatment.